A Study on Evidence-based Decision Making in Hospitals of Haryana (Indian Journal of Extension Education, 2021)
In India, healthcare is one of the largest sectors in concerning to revenue and employment. It comprises of hospitals, medical devices, clinical trials, outsourcing, telemedicine, medical tourism, health insurance and medical equipment. The study was conducted to discover Evidence-based Decision Making in Public and Private hospital sector. The objective was to determine the various factors affecting the Evidence-based Decision Making and to know the significant difference for various demographic factors for challenges faced in Evidence-based Decision Making. The value of ANOVA indicated that the doctors, nurses and administration staff with different salary have different opinion regarding the challenges on evidence-based decision making. In decision making process goal orientation should be the prime factor to be considered.